Application of two kinetic methods to evaluate the trap energy of lithium fluoride plus sodium fluoride thermoluminescent phosphor - Selcuk, A (Kluwer Academic Publ, 1997)
A mixture of equal quantities of powdered LiF and NaF was doped with 0.2% each of Ti, Mg and Mn and heated to obtain a LiF+NaF phosphor. After grinding and sieving, the thermoluminescent phosphor was used to obtain the thermoluminescence characteristics such as the glow curve; the dose-response curve, sensitivity, reproducibility and linearity were all established. The main goal was to introduce two new methods for the calculation of trap energy: the single-peak-differential and single-peak-integration methods, both modifications of the basic method of Randall-Wilkins. The plots used to calculate the trap energy were In[(d alpha/dT)1/(1-alpha)] vs. 1/T and ln[ln(1-alpha)/(T-0-T)] vs. 1/T, respectively. These linear plots with slopes of (E/k) gave trap energies of E=0.547 eV and E=0.551 eV, respectively.
Keywords: LiF; NaF; thermoluminescence; trap energy